Carbamazepine, phenytoin, and oral anticoagulants: Drug‐drug interaction and clinical events in a retrospective cohort. Issue 2 (17th February 2022) - Candeloro, Matteo; Eikelboom, John W.; Chan, Noel; Bhagirath, Vinai; Douketis, James D.; Schulman, Sam
Abstract: Background: Carbamazepine and phenytoin are potent inducers of enzymes that metabolize oral anticoagulants. Objectives: To determine the clinical impact of drug‐drug interactions between these anticonvulsants and oral anticoagulants, and whether they affect the treatment with direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs). Material and methods: Data on patients cotreated with carbamazepine or phenytoin and an oral anticoagulant were retrospectively retrieved from medical records from 2011 to 2020. Outcomes were time in therapeutic range (TTR), DOAC levels, thromboembolic events, major bleeding, and all‐cause mortality. Results: Among 85 patients (37% female, median age 68 years) treated with carbamazepine ( n = 43 [51%]) or phenytoin ( n = 42 [49%]), 53 (62%) were initially treated with VKAs and 32 (38%) with DOACs. TTR in VKA patients was 63%, which improved in year 2. Four of seven trough and five of 12 peak DOAC plasma levels were lower than expected. The incidence rate (95% confidence interval) per 100 person‐years for thromboembolism was 3.6 (3.1‐4.2) for VKA patients and 4.4 (3.5‐5.6) for DOAC patients; for major bleeding 1.8 (1.5‐2.1) and 1.5 (1.2‐1.9), and for all‐cause mortality 3.6 (3.1‐4.2) and 1.5 (1.2‐1.9), respectively. Incidence rates between VKAs and DOACs and between carbamazepine and phenytoin were similar. Conclusion: There was a high incidence of thromboembolism in patients cotreated with anticoagulants and carbamazepine or phenytoin. The incidence rates of thrombotic and bleeding events were similar between VKA and DOAC patients. DOAC levels were lower than expected in 47% of cases tested, without correlation with clinical outcomes.